Modelling of defects in aluminium cast products. (January 2022) - Jolly, Mark; Katgerman, Laurens
Abstract: Over the last 4 decades, remarkable progress has been made in the modelling of casting processes. The development of casting models is well reflected in the proceedings of the 15 Modelling of Casting, Welding and Advanced Solidification Processes (MCWASP) conferences that have been held since 1980. Computer simulations have enabled a better understanding of the physical phenomena involved during solidification. Modelling gives the opportunity to uncouple the physical processes. Furthermore, quantities that are difficult or impossible to measure experimentally can be calculated using computer simulations e.g. flow patterns and recalescence. However, when it comes to accurately predicting casting performance and in particular, the occurrence of defects like cracks, segregation and porosity there is certainly some way to go. In this paper, the current understanding of the main mechanisms of defect formation during shape and DC casting processes will be reviewed and requirements will be discussed to give a direction to making casting models more predictive and quantitative.